Exploring How Cultural Identity Shapes Consumer Social Well-Being and Feedback Behavior through a Cognitive–Affective–Behavioral Framework - Lingling Cai; Zong-Yi Zhu (Environment and Social Psychology, 2025)
Guochao culture is defined as the fusion of old Chinese cultural symbols with modern design and branding, which is a trend of a youth-oriented national style. Guochao culture has rapidly emerged as a major channel for youth to express identity and cultural values. This study examines how cultural identity, cultural confidence, and well-being shape Generation Z’s feedback behavior in the Guochao context. Using the cogni-tive-affective-behavior (CAB) framework, it analyzes how cognitive factors (cultural identity) influence affec-tive states (spiritual and social well-being), which in turn drive behavioral responses. The research further ex-plores the moderating effect of nostalgia on cultural engagement. A total of 121 valid survey responses were collected from students at Hainan Normal University, and the data were analyzed with the support of structural equation modeling. Even though the size of samples is small, it can be considered as the appropriate size in the context of the PLS-SEM since it is an appropriate exploratory model with small sample size. Findings show that cultural pride, spiritual well-being, and social well-being act as sequential mediators between cultural identity and feedback behavior, whereas cultural praise does not exhibit this mediating role. Nostalgia was found to moderate these relationships, with stronger effects observed among respondents reporting lower levels of nos-talgia. Overall, cultural identity exerts a significant indirect influence on feedback behavior through cultural pride and well-being, while nostalgia conditions these effects. These results provide theoretical insights into consumer behavior research and practical guidance for brand marketers engaging with Generation Z.